Effect of Green-biosynthesis Aluminum Nanoparticles (Al NPs) on Salmonella enterica Isolated from Baghdad City (Baghdad Science Journal, 2023)
This study is aimed to Green-synthesize and characterize Al NPs from Clove (Syzygium aromaticumL.) buds plant extract and to investigate their effect on isolated and characterized Salmonella enterica growth. S. aromaticum buds aqueous extract was prepared from local market clove, then mixed with Aluminum nitrate Al(NO3)3. 9 H2O, 99.9% in ¼ ratio for green-synthesizing of Al NPs. Color change was a primary confirmation of Al NPs biosynthesis. The biosynthesized nanoparticles were identified and characterized by AFM, SEM, EDX and UV–Visible spectrophotometer. AFM data recorded 122nm particles size and the surface roughness RMs) of the pure S. aromaticum buds aqueous extract recorded 17.5nm particles size, while the results of Al NPs in the tested sample recorded 21nm particles size with surface roughness RMs about 2.35nm. SEM images revealed the presence of Al NPs with diameters ranged from 33.5-70.4nm with regular spiracles shape particles in the prepared biosynthesized nanoparticle sample. The EDX spectrum analysis showed that the Aluminium weight ratio was 1.75, while it was 50.498 in the Al NPs sample prepared from aqueous extract. UV-Visible spectroscopy data revealed that biosynthesized Al NPs were absorbed at 213nm while Aluminum nitrate was absorbed at 258nm. These results indicate the formation of Al NPs. The antibacterial activity showed that Al NPs exhibited having high antibacterial activity on Salmonella spp. isolates compared to the effect of the control agent (imipenem) in this experiment. We conclude that biosynthesized Al NPs from clove aqueous extract can be exploited as natural antibacterial compounds to inhibit the growth of Salmonella.